Imagine-Self Perspective-Taking and Rational Self-Interested Behavior in a Simple Experimental Normal-Form Game - Karbowski, Adam; Ramsza, Michał (Frontiers in Psychology, 2017)
The purpose of this study is to explore the link between imagine-self perspective-taking and rational self-interested behavior in experimental normal-form games. Drawing on the concept of sympathy developed by Adam Smith and further literature on perspective taking in games, we hypothesize that introduction of imagine-self perspective-taking by decision-makers promotes rational self-interested behavior in a simple experimental normal-form game. In our study, we examined behavior of 404 undergraduate students in the two-person game, in which the participant can suffer a monetary loss only if she plays her Nash equilibrium strategy and the opponent plays her dominated strategy. Results suggest that the threat of suffering monetary losses effectively discourages the participants from choosing Nash equilibrium strategy. In general, players may take into account that opponents choose dominated strategies due to specific not self-interested motivations or errors. However, adopting imagine-self perspective by the participants leads to more Nash equilibrium choices, perhaps by alleviating participants’ attributions of susceptibility to errors or non-self-interested motivation to the opponents.